Comparative Analysis Of Income From Online And Offline Buying And Selling Business In The Perspective Of Shariah Economics (Case Study At CV. Global best LS) - Ahmad Dairobi; Abdulah Safe’i; Suhendi (International Journal of Business and Quality Research, 2025)
The development of information technology, especially the internet, has driven a significant transformation in buying and selling activities. Business actors now do not only rely on physical stores (offline), but also utilize digital media to promote and sell products online. This change has an impact on the structure of business income, including at CV. Global Best LS which implements both models. Differences in terms of market reach, patterns of interaction with consumers, and cost efficiency between online and offline methods raise questions about the extent to which each is effective in increasing income. Based on this, this study aims to examine in more depth the comparison of online and offline business income within the framework of sharia economics. The purpose of this study is to analyze the comparison of income between online and offline buying and selling businesses at CV. Global Best LS, identify the factors that influence these differences, and evaluate the level of application of sharia economic principles in the two business models. This study is based on sharia economic theory, especially in the context of buying and selling (al-bai'), which emphasizes the principles of honesty, justice, and blessings in every transaction. In addition, this study also refers to the approach of consumer behavior theory and marketing strategies in digital business to support comparative analysis of business income between online and offline buying and selling models. The method used is descriptive qualitative research, with a case study approach at CV. Global Best LS. Data was collected through in-depth interviews, observations, and documentation, then analyzed narratively to obtain a factual picture of the income from the two buying and selling methods run. The results of the study show that online buying and selling businesses generate higher income compared to offline businesses, due to wider market reach, operational efficiency, and digitalization trends. Meanwhile, offline businesses have the advantage of building consumer trust through direct interaction, although constrained by high operational costs. Both of these buying and selling methods have implemented the principles of Islamic economics in general, although improvements are still needed in terms of financial recording and transaction transparency.